Personâ€™s Spiritual Being in the Context of the Cossack Life-long Learning - Vladimirovich Kondratiev, Sergey; Aleksandrovna Moiseeva, Olga; Nikolaevich Kuraev, Alexey; Vladimirovich Ivanov, Mikhail; Victorovna Gudkova, Anastasia (International Journal of Engineering and Technology, 2018)
This article considers liberalism as an ideology that contradicts traditional morality. The authors have distinguished the problems of personal being in the conditions of liberalism. In this regard, the â€œCossack upbringingâ€ is presented as a way to confront the liberal ideology, form and develop the personality of a true patriot and citizen.Â Â